2011
DOI: 10.1038/nature10631
|View full text |Cite
|
Sign up to set email alerts
|

A compact system of small planets around a former red-giant star

Abstract: Planets that orbit their parent star at less than about one astronomical unit (1 AU is the Earth-Sun distance) are expected to be engulfed when the star becomes a red giant. Previous observations have revealed the existence of post-red-giant host stars with giant planets orbiting as close as 0.116 AU or with brown dwarf companions in tight orbits, showing that these bodies can survive engulfment. What has remained unclear is whether planets can be dragged deeper into the red-giant envelope without being disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
203
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(206 citation statements)
references
References 28 publications
3
203
0
Order By: Relevance
“…Examples are the 1.25 MJ planet (where MJ is the mass of Jupiter) orbiting 0.116 au from a horizontal branch star (Setiawan et al 2010), two Earth-sized objects orbiting a subdwarf B star at a separation of 0.0060 and 0.0076 au (Charpinet et al 2011), or three earth-sized planets orbiting a subdwarf B pulsator (Silvotti et al 2014). These planets must have been engulfed in the envelope of the giant star that became the subdwarf star today.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are the 1.25 MJ planet (where MJ is the mass of Jupiter) orbiting 0.116 au from a horizontal branch star (Setiawan et al 2010), two Earth-sized objects orbiting a subdwarf B star at a separation of 0.0060 and 0.0076 au (Charpinet et al 2011), or three earth-sized planets orbiting a subdwarf B pulsator (Silvotti et al 2014). These planets must have been engulfed in the envelope of the giant star that became the subdwarf star today.…”
Section: Introductionmentioning
confidence: 99%
“…These planets must have been engulfed in the envelope of the giant star that became the subdwarf star today. Charpinet et al (2011) and Passy et al (2012b) showed how planets may have been much more massive initially and lost much of their mass in the CE phase. However, they could not determine how the core of the planets survived the interaction instead of plunging into the core of the giant.…”
Section: Introductionmentioning
confidence: 99%
“…Villaver & Livio 2009;Nordhaus & Spiegel 2013). For example, Charpinet et al (2011) have used Kepler to deduce the presence of two Earth-sized planets orbiting a hot B subdwarf star (a red giant stripped of its envelope, and destined to become a WD), with 5.7 hr and 8.2 hr periods. Reflection or thermal re-emission of the WD radiation by the planets modulates the WD light by ∼ 50 ppm.…”
Section: Close Companions To Wdsmentioning
confidence: 99%
“…However, little is known about the evolution of planetary systems beyond the main sequence lifetime of their host stars. Planets have been discovered around (sub)giant stars (Johnson et al 2011;Gettel et al 2012) and horizontal branch stars (Silvotti et al 2007;Setiawan et al 2010;Charpinet et al 2011). There is only one planetarymass object detected with direct imaging around a white dwarf (WD 0806-661;Luhman et al 2011), although theoretical calculations show that many more planets can survive the red giant stage (Burleigh et al 2002;Jura 2008;Mustill & Villaver 2012;Nordhaus & Spiegel 2013).…”
Section: Introductionmentioning
confidence: 99%